2011
DOI: 10.1111/j.1439-0396.2011.01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term effect of dietary yeast nucleotide supplementation on small intestinal enzyme activities, bacterial populations and metabolites and ileal nutrient digestibilities in newly weaned pigs*

Abstract: In previous studies, dietary nucleotides have been shown to improve performance in single-stomached animals by promoting the renewal of small intestine epithelial cells and by influencing the activity and composition of the microbial community in the digestive tract. The present experiment was carried out with 12 barrows weaned at the age of 18 days and fitted with a simple T-cannula at the distal ileum. To determine short-term effects of dietary yeast nucleotides, the piglets received a grain-soybean meal-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
0
17
0
3
Order By: Relevance
“…Moreover, the secretion of digestive enzymes by the pancreas is influenced by the nucleotide pool in pancreatic cells since nucleotides are needed for RNA synthesis which precedes protein synthesis (Schulz and Stolze 1980). Moreover, digestibility studies involving supplemental NRYE in pigs are not available to compare with our results except that of Sauer et al (2012) which reported no effects of pure nucleotides on apparent ileal digestibilities of CP, DM, and crude fiber in piglets. Studies have shown that AGP ( Jensen et al 2014) and NRYE (Martinez-Puig et al 2007) increase villous height and villous/crypt ratio in the small intestine of pigs thereby enhancing nutrient absorption.…”
mentioning
confidence: 64%
“…Moreover, the secretion of digestive enzymes by the pancreas is influenced by the nucleotide pool in pancreatic cells since nucleotides are needed for RNA synthesis which precedes protein synthesis (Schulz and Stolze 1980). Moreover, digestibility studies involving supplemental NRYE in pigs are not available to compare with our results except that of Sauer et al (2012) which reported no effects of pure nucleotides on apparent ileal digestibilities of CP, DM, and crude fiber in piglets. Studies have shown that AGP ( Jensen et al 2014) and NRYE (Martinez-Puig et al 2007) increase villous height and villous/crypt ratio in the small intestine of pigs thereby enhancing nutrient absorption.…”
mentioning
confidence: 64%
“…Sauer et al [20] and Andrés-Elias et al [21] supplemented 0.1 and 0.15 % yeast extract in piglet starter diets, respectively, and reported no effect of yeast extract on growth performance. Between d 7 and 11 (post-challenge), the LPS challenge reduced ADG, ADFI and G:F of CC pigs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the histological analysis showed feeding nucleotides-enriched YP did not markedly affect intestinal morphology, as an indicator to reflect the renewal rate of intestinal epithelial cells. Previous studies by Van der Peet-Schwering et al (2007) and also Sauer et al (2012b) indicated that dietary nucleotides failed to improve intestinal morphology, but some other studies showed there was a positive effect of dietary nucleotides on intestinal repair under certain stress conditions (Bueno et al 1994). It is generally accepted that the intestinal response to nucleotides may vary depending on the health status of animals.…”
Section: Discussionmentioning
confidence: 99%
“…may be beneficial for animal growth and intestinal health by enhancing gut integrity and body immunity (Owens and McCracken 2007). For instance, dietary nucleotide supplementation has been shown to improve growth performance, immune response, and anti-oxidative capability of piglets (Salobir et al 2005;Superchi et al 2012;Sauer et al 2012b).…”
Section: Introductionmentioning
confidence: 99%